Idiopathic Thrombocytopenic Purpura after Mastectomy and Axillary Lymph Node Dissection - Wil L. Santivasi; Meghan M. Routt; Alicia M. Terando (Case Reports in Surgery)
First described in 1916, idiopathic thrombocytopenic purpura (ITP) is an autoimmune disease resulting in the destruction of platelets. Here, we present a case of an 85-year-old patient diagnosed with invasive ductal carcinoma of the breast whose surgical treatment was complicated postoperatively by acute-onset thrombocytopenia with a resultant hematoma at the operative site. Diagnostic Workup revealed no clear etiology for the thrombocytopenia; therefore, a presumptive diagnosis of idiopathic thrombocytopenic purpura was made. Previous literature has associated the development of idiopathic thrombocytopenic purpura with breast cancer. However, to the authors’ knowledge, there are no reported cases of ITP presenting immediately following surgical intervention for breast cancer in the absence of other etiologic factors.